(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The main investigation-to study the frequency of subclinic Cushingoid at women with polycystic ovaries syndrome (PCOS) Material and methods of investigation.120 patients of fertile age were examined with polycystic ovary syndrome (PCOS).. Middle age of patients - 25.5 ± 4. 3 years. . The remoteness of disease doubted within limits from 7 months to 9 years. 20 healthy women of corresponding age made a control group. The complex of researches, including clinical (global analysis of blood and urine), biochemical (glucose of blood, test of tolerance to glucose) hormonal (LH, FSH, prolactin, estradiol, progesteron, free orchidic hormone, dehydroepiandrostendion (DHEA), 17 –oxyprogesterone, antimuller hormone (AMH), insulin on 14 day of cycle), was executed all patients, ULTRASONIC of uterus and ovaries (transabdominal and transvaginal) on 14 day of cycle with follikulometriya in a dynamics, and also MRI of pituitary. Results.Patients were divided into three groups: 1 group. are patients with primary PCOS- 23 cases (19%), 2 gr. are patients with secondary PCOS at obesity are 89 cases (74%), 3 gr. are patients with secondary PCOS and subclinical Cushingoid are 8 cases (7%). A control group is 20 women of similar age. In our research prevailed on the whole 2 degree of obesity in 2 and 3 groups of patients - 53 cases from 120 (44.1%). In the 1 group of patients the reliable decline of both pituitary and ovarian hormones registered on a background of hyperandrogenemia. So, as compared to the group of control on the 14th day of cycle were for LH, FSH, IGF-1 and also estradiol, progesterone, while free testosterone, DGEA - were enhanceable as compared to control data. Further in the second group of patients the reliable decline of pituitary hormones was also educated on a background hyperandrogenemia, while an ovarian function was within the limits of norm. So, as compared to the group of control on the 14 day of cycle In the third group of patients, the reliable decline of pituitary hormones was also educated on a background hyperandrogenemia, while an ovarian function was within the limits of norm. So, as compared to the group of control on the 14th day of cycle were for LH, FSH, IGF-1, here free testosterone, DHEA, 17 OKS, insulin, - were for certain enhanceable as compared to control data. Conclusions.1) Frequency of met subclinical Cushing among women with PCOS 6.6% is equal. ; 2) In all groups on 14 day of cycle the reliable decline of basale values of for LH, FSH, IGF-1 was marked, progesterone, estradiol on a background hyperandrogenemia (enhanceable level of free testosterone.). Thus in 2 and 3 groups a hyperinsulinemia was marked. Only for patients 3 groups were marked for certain enhanceable values of DHEA, 17 OKS and cortisol of blood. Mean values of prolactin, AMG were in a norm. 3) a further supervision is Needed in a dynamic after probability of renewal of fertile function in all groups of patients with PCOS